Association of pulmonary artery bifurcation angle shift with contralateral stenosis after post-arterial switch in the pediatric transposition of great artery patients - Panupong Seripanu; Tanop Srisuwan; Yupada Pongprot; Rekwan Sittiwangkul; Thanaporn Phanacharoensawad; Pakpoom Wongyikul; Phichayut Phinyo; Kwannapas Saengsin (PLoS ONE, 2025)
Background The arterial switch operation (ASO) is the standard surgical treatment for transposition of the great arteries (TGA). Postoperative complications such as branch pulmonary artery (PA) stenosis are commonly observed. This study aimed to investigate the possible potential anatomical mechanisms contributing to isolated branch PA stenosis using cardiac computed tomography (CCT). Methods A retrospective, single-center study was conducted on pediatric patients under 18 years of age diagnosed with TGA, with or without ventricular septal defect (VSD), who underwent ASO and cardiac CCT between January 2004 and October 2022. Baseline characteristics, echocardiographic data, and CCT findings were compared between patients with and without isolated branch PA stenosis. Special attention was given to the angle between the PA bifurcation and the ascending aorta (AAO). Results Among 30 patients enrolled, 46.67% (14/30) had isolated branch PA stenosis, while 53.33% (16/30) had no stenosis. Baseline and echocardiographic variables showed no significant differences between groups, except for the PA bifurcation angle relative to the AAO. Patients with isolated right PA (RPA) stenosis demonstrated significantly greater leftward angulation (median angle: 25° [IQR: 24, 30]) compared to the no-stenosis group (median angle: −2° [IQR: −8, 6.5]). Similarly, isolated left PA (LPA) stenosis was associated with greater rightward angulation (median angle: −22° [IQR: −32, −20]) compared to the no-stenosis group (P = 0.042). Conclusion Alterations in the PA bifurcation angle relative to the AAO may contribute to the development of isolated branch PA stenosis following ASO. Preoperative planning to optimize the PA bifurcation angle to within ±20 degrees may help reduce the risk of postoperative stenosis. A larger study incorporating advanced cardiac imaging into routine ASO follow-up is warranted.